Assistance in Designing Elementary School Learning By Integrating Literacy And Numeracy - Suryanti, Suryanti; Lutfi Choirunnisa, Nadia; Gunansyah, Ganes; Indartiningsih, Duhwi; Khairiyah, Ummu (Asosiasi Dosen Pengembang Masyarajat (ADPEMAS) Forum Komunikasi Dosen Peneliti, 2024)
In the era of the Industrial Revolution 4.0, the learning process must develop students' literacy and numeracy skills. Teachers need to design learning activities that integrate literacy and numeracy. Training and mentoring for teachers are required to understand the context of literacy and numeracy and how to create learning that incorporates literacy and numeracy. The problems experienced by these partners were used as the basis for the team to provide training and assistance to MINU KH Mukmin Sidoarjo teachers in the form of community service activities. This community assistance uses the Service Learning approach to enhance teachers' capacity in designing learning by integrating literacy and numeracy. The teacher's learning design is then implemented and evaluated. Based on the results of design analysis and observation of learning in the classroom, it can be concluded that teachers have been able to analyze and design learning by integrating literacy and numeracy